EDUKASI MAKANAN SEHAT PUJAAN HATI GUNA MENINGKATKAN STATUS GIZI DI PUSKESMAS GUNUNG ANYAR SURABAYA: EDUKASI MAKANAN SEHAT PUJAAN HATI GUNA MENINGKATKAN STATUS GIZI DI PUSKESMAS GUNUNG ANYAR SURABAYA - Wahyuni Dyah Parmasari; Sukma Sahadewa; Devi Dwi Rianti, Emilia (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2024)
Development will develop based on quality resources, so it must have humans with good nutritional status and in essence it starts from when they are still in the womb. Nutrition is one of the things that affects human health, where ideal nutrition is related to the development of intelligence, health, skills and supports normal child growth according to their age. The aim is to further socialize and provide insight through healthy food education